Equipamiento etnicocultural, zona urbana de Santa Marta, Magdalena (Colombia) - Rincón Villaquira, Marcela del Pilar (Universidad Antonio Nariño, 2021)
The Arhuaca indigenous community located in the department of Magdalena, in the foothills of the Sierra Nevada de Santa Marta, shows its territory with a high sense of belonging, seeking to teach and provide knowledge, and the conservation of its cosmology and traditions. The way to see the world of the Iku indigenous reservation (Arhuaca), is to visualize their lands as the most precious, understood in a holistic way. Despite its own characteristics, at present, a series of conflicts with traditions, language, architecture, beliefs, religion, etc. have been generated. It should be mentioned that the above as a product of globalization and the advancement of technologies, which generate influence and intervene in indigenous communities in general. In this project research, an EthnicCultural equipment is proposed for the indigenous reservation of Iku, through an architectural element, whose design relates the interpretation of the worldview; according to the investigations carried out in the participatory rural work of the place of study. The collection of information was fundamental for the development of the equipment since different questions and a series of possible answers to them arose thanks to this, either through flexible spaces that allow the community to appropriate community spaces or certain buildings designed with a productive end.